Enhancing Sustainability in Potato Crop Production: Mitigating Greenhouse Gas Emissions and Nitrate Accumulation in Potato Tubers through Optimized Nitrogen Fertilization - Seno Nascimento, Camila [UNESP]; Seno Nascimento, Carolina [UNESP]; de Jesus Pereira, Breno [UNESP]; Soares Silva, Paulo Henrique [UNESP]; Pessôa da Cruz, Mara Cristina [UNESP]; Bernardes Cecílio Filho, Arthur [UNESP] (MDPI, 2024)
The complex ramifications of global climate change, which is caused by heightened concentrations of greenhouse gases in the Earth’s atmosphere, are deeply concerning. Addressing this crisis necessitates the immediate implementation of adaptive mitigation strategies, especially within the agricultural sector. In this context, this study aimed to assess how the supply of nitrogen (N) (0, 70, 140, and 210 kg N ha−1) in the forms of ammonium nitrate and urea affects the agronomic performance, food quality, greenhouse gas emissions (GHG), and carbon footprint of potato plants. The examined hypothesis was that by precisely calibrating N doses alongside appropriate sourcing, over-fertilization in potato cultivation can be mitigated. A decline in stomatal conductance and net photosynthetic rate disturbs physiological mechanisms, reflecting in biomass production. Application of 136 kg N ha−1 as urea showed a remarkable yield increase compared to other doses and sources. The highest nitrate content in potato tubers was achieved at 210 kg N ha−1 for both sources, not exceeding the limit (200 mg kg−1 of fresh mass) recommended for human consumption. The lowest carbon footprint was obtained when 70 kg N ha−1 was applied, around 41% and 26% lower than when 210 kg N ha−1 and 140 kg N ha−1 were applied, respectively. The results demonstrated that over-fertilization not only worsened the yield and tuber quality of potato plants, but also increased greenhouse gas emissions. This information is valuable for establishing an effective fertilization program for the potato crop and reducing carbon footprint.
Keywords: ammonium nitrate; CO2 equivalent; global warming potential; Solanum tuberosum; urea